IMPROVING THE ACCOUNTING (BALANCE) OF REAL ESTATE OBJECTS IN SETTLEMENTS: A MULTIFACETED APPROACH (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Efficiently accounting for real estate objects within settlements is crucial for effective urban planning, property management, taxation, and overall economic development. Here's a breakdown of key areas to focus on for improvement: